2022
DOI: 10.3389/fchem.2022.871509
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights Into the Sulfated Glucuronic Acid-Based Anti-SARS-CoV-2 Mechanism of Exopolysaccharides From Halophilic Archaeon Haloarcula hispanica

Abstract: The pandemic caused by SARS-CoV-2 is the most widely spread disease in the 21st century. Due to the continuous emergence of variants across the world, it is necessary to expand our understanding of host–virus interactions and explore new agents against SARS-CoV-2. In this study, it was found exopolysaccharides (EPSs) from halophilic archaeon Haloarcula hispanica ATCC33960 can bind to the spike protein of SARS-CoV-2 with the binding constant KD of 2.23 nM, block the binding of spike protein to Vero E6 and bronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…EPSs extracted from the parental strain consists of GlcA, Man, Gal, and Glc at a 4:3.6:1.5:1 M ratio. However, analysis of the EPS from the Δ HAH_1206 mutant showed only trace amounts of GlcA could be detected ( 35 ). To further assess whether HAH_1206 contributes to acidic EPS synthesis, DolP-linked sugars in the parental and mutant strains were extracted from the cell membrane, released with hydrofluoric acid, and analyzed by HPAEC-pulsed amperometric detection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…EPSs extracted from the parental strain consists of GlcA, Man, Gal, and Glc at a 4:3.6:1.5:1 M ratio. However, analysis of the EPS from the Δ HAH_1206 mutant showed only trace amounts of GlcA could be detected ( 35 ). To further assess whether HAH_1206 contributes to acidic EPS synthesis, DolP-linked sugars in the parental and mutant strains were extracted from the cell membrane, released with hydrofluoric acid, and analyzed by HPAEC-pulsed amperometric detection.…”
Section: Resultsmentioning
confidence: 99%
“…5 ), the sugar donors for the negatively charged sugars of the acidic EPS. Indeed, only trace amounts of GlcA could be detected in the EPS from the Δ HAH_1206 mutant ( 35 ). Therefore, it is reasonable to conclude that AepG is required for the synthesis of the negatively charged sugars of the acidic EPS, which is required for the separation and dispersal of H. hispanica cells in hypersaline surroundings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In preclinical studies of viral infections, heparin possesses a direct antiviral activity upon SARS-CoV-2. The early reports indicated that heparin could bind to the proteolytic cleavage site of the S1 and S2 protein based on combined surface plasmon resonance (SPR) and computational study [15] , [16] . Zhang et al found that heparin, HS, and non-anticoagulant low molecular weight heparin at micromolar doses could effectively compete with spike glycoprotein of COVID-19 to block the viral invasion pathway [17] .…”
Section: Sars-cov-2 and Heparinmentioning
confidence: 99%